Charting a new course with plasmon-mediated chemistry - Christa L. Brosseau; Emiliano Cortés (Communications Chemistry)
Communications Chemistry is pleased to introduce a Collection of articles on the topic of plasmon-mediated chemistry. Here, the Guest Editors discuss different themes within and look towards the future of the field.